ORGANIZATION OF LEISURE OF CHILDREN RAISED IN FAMILY CONDITIONS - N.V. Kovalevska (Academy of Cognitive and Natural Sciences, 2009)
The article is devoted to a problem of definition of features of leisure organization for children, who are educated in families. The tructure requirements for its organization, its contest and forms are analyzed in the article. The role of family teacher in organization of pre-schoolers free time is deuiled.